Studi Komparatif Kebijakan Luar Negeri Indonesia Bebas-Aktif dan Lebih Dekat ke Salah Satu Blok, Mana Yang Lebih Menguntungkan Kepentingan Nasional Indonesia? - Syahdami, Syahdami; Rofii, Muhammad Syaroni, Mr. (Jurnal Kajian Stratejik Ketahanan Nasional, 2022)
Since independence, Indonesia's foreign policy has always changed. Although the doctrine of a free and active foreign policy that was first coined by the proclaimer Mohammad Hatta in 1948 has never changed, its practice depends on the approaches and interpretations taken by the ruling leaders. The old order leaned towards the eastern bloc, the new order tilted towards the western bloc, and the reform order was in a dilemma due to various domestic and international factors. Of the various political choices that have been made by the Indonesian authorities, which one is more beneficial to Indonesia's own national interests. This is the main concern of this article. Keywords: free-active foreign policy, old order, new order, reform, national interest